The impact of maternal depression during pregnancy on the risk of gestational diabetes mellitus: a meta-analysis - Du, Nan; Dai, Limin; Xu, Min; Guan, Tingting (Frontiers in Endocrinology, 2025)
BackgroundAntenatal depression, defined as clinically significant depressive symptoms occurring during pregnancy, has been suggested to increase the risk of gestational diabetes mellitus (GDM), a glucose intolerance disorder with onset or first recognition during pregnancy. However, evidence regarding its relationship with GDM remains inconsistent. This meta-analysis aimed to quantitatively assess the association between antenatal depression and the risk of GDM.MethodsWe systematically searched PubMed, Embase, Wanfang, and the Cochrane Library from inception to June 12, 2025, for observational studies reporting the association between depression during pregnancy and GDM. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model.ResultsA total of eight studies were included in the meta-analysis. The pooled analysis showed that maternal depression during pregnancy was significantly associated with an increased risk of GDM (OR = 1.37, 95% CI: 1.20-1.54). Subgroup analyses based on country, depression assessment tool, and study design showed consistent results. Sensitivity analyses confirmed the stability of the results. No significant publication bias was detected.ConclusionThis meta-analysis suggests that maternal depression during pregnancy is associated with a significantly increased risk of developing GDM. Screening for depression in early pregnancy may represent a potential strategy to reduce the risk of GDM and improve maternal health outcomes.